RETRACTED: Establishing markers of avoidant behavior in the context of developing sustainable behavior - Godunov Mikhail; Portnov Evgeny (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001